Benih Keturunan Induk Ikan Nila yang Divaksinasi pada Tingkat Kematangan Gonad-2 Lebih Tahan Terhadap Infeksi Streptococcus agalactiae (RESISTANCE OF TILAPIA (OREOCHRIMIS NILOTICUS) FRY VACCINATED AT DIFFERENT GONADAL DEVELOPMENTAL STAGES TOWARD STREPTOCO - Nissa, Khairun; Sukenda, Sukenda; Junior, Muhammad Zairin; Lusiastuti, Angela Mariana; Nuryati, Sri (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
The aim of this study was to evaluate the effectiveness of vaccination based on gonad maturationstages on tilapia brood stocks in which the released antibodies was able to be transferred to the seed.Vaccine composed with whole cells and extracellular product (ECP) was injected at stage 2 and stage 3 ofthe gonad development stages at concentration of 109 CFU mL1 as much as 4 mL to 1 kg of brood fish.Control fish was unvaccinated treatment. Challenge study at seed was conducted by immersing S. agalactiaefor 30 minutes at 7, 14, 21, and 28 days post hatching (DPH) in 107 CFU/mL. Antibody levels on broodstocks, eggs, and body fluids of seed, and relative percentage survival (RPS) of seed post challenge studywere evaluated. The results showed that stage 2 of gonad developmental stages was found on 7 days postinitial spawning and stage 3 found on 14 days post initial spawning of brood fish. Vaccinated done in stage 2 of gonad developmental stages gave immunoglobulin serum in brood (0,166±0,001), egg (0,165±0,002),and seed aged 7, 14, 21, and 28 days post hatching (0,164±0,002, 0,162±0,005, 0,155±0,006, and 0,14±0,008respectively) were significantly higher (P<0,05) compared to other treatment. Challenged test that doneby immersing with S. agalactiae suspension on larval aged 7, 14, 21, and 28 days had highest RPS(95,24%, 83,33%, 72,22%, and 56,02% respectively) formed on seed from brood stock vaccination in gonaddevelopment stage 2. Vaccination in tilapia brood stocks at stage 2 of gonad developmental stages gavehighest protection by maternal immunity to the seed against S. agalactiae.
Keywords: tilapia; Streptococcus agalactiae; gonad developmental stage; vaccine, maternal immunity